An An analysis of the adoption of online learning in universities; a case of the Cavendish University Learning Platform (CU-LP) - Ambrose, Arinaitwe (Journal of Social Review and Development, 2022)
The adoption of online learning as a prerequisite to continuous education is new among most universities in Uganda. Although its adoption is mandatory for teaching and learning, online learning has been hard to embrace because the training facilitators or teachers to embrace the new technologies and students learning how to use and afford the process is a challenge (Kituyi & Robert 2012). Since the covid-19 pandemic outbreak, a number of universities have tried to promote electronic learning environments and adopt e-learning systems like Moodle, melimu, and others to aid teaching and learning. The paper presents results from a study conducted using a mixed methods (qualitative and quantitative) approach to the adoption of online learning in Universities in Uganda. The data collection methods adopted a demanding systematic scientific inquiry based on; facts, analysis, and reporting. Of the 2241 target respondents, 2129 (2025 students, 104 lecturers, and non-teaching academic staff) participated in the study with a response rate of 95%. The findings of the study showed that the factors influencing the acceptance and use of e-learning platforms as a tool of teaching and learning range from training to and adoption of technologies using gadgets like laptops, smartphones, and others. The approaches adopted to monitor student learning on e-learning systems ranged from frequent training on the use of the platform and constant feedback.